P201 Single-Port VATS Lobectomy. Minimising Minimally Invasive Surgery. (19th November 2012) - Socci, L; Quereshi, A; Wake, P; Malik, M; Internullo, E; Rivas, D Gonzalez; Martin-Ucar, AE
Abstract : Introduction: Only around 10% of lobectomies in the UK are performed by VATS via 3 or 4 incisions. We now offer routinely VATS lobectomy via a very novel single port access to our patients. Methods: We aim to evaluate the early outcomes of our initial experience with Single-Port VATS lobectomy. From December 2011 until July 2012, 24 cases [13 male and 11 female, age 68 (45–85)years] were intended to undergo lobectomy via Single-Port technique. Data in Median (Range). Results: Thoraco score was 1.57 (0.1–11.8)and FEV1 was 74 (34–157) % predicted. Thirteen operations were right-sided (5 upper, 2 middle and 6 lower lobectomies), and eleven left-sided (6 upper and 5 lower). Operations lasted 127 (65–194)minutes. One intercostal drain was used in all cases, and it was removed at 3 (1–9)days. Patients were discharged home at 3 (range 1–21) days. There was one postoperative death in our experience, a patient who was ready for discharge 3 days after surgery when he suffered a dense middle cerebral artery stroke that led to his death by contralateral pneumonia 20 days later. One case was converted to thoracotomy due to bleeding and another case a retractor was used in the incision to enable safe suture of a branch of the pulmonary artery after partial failure of the stapler. In 10 of the 24 patients the patients started oral analgesia on the day of surgery without the use of epidurals or paravertebral catheters. Conclusion: Single-Port VATS lobectomy is feasible and safe. It is becoming our approach of choice for early stage lung cancer due to its low incidence of complications and the very fast recovery with some patients going home as early as the day after surgery. This technique will make the case for surgery against newest techniques of radiotherapy for lung cancer.